Pengaruh Frekuensi Pemberian Air Irigasi Terhadap Produktivitas Caisim Hidroponik dengan Media Sekam Bakar di PT. Momenta Agrikultura Lembang - Epri Hartono; Muhammad Idrus (Jurnal Ilmiah Teknik Pertanian - TekTan, 2015)
The experiment was conducted at the PT. Momenta Agricultura Lembang Jawa Barat from March  to April 2014.  The objective of the research were to study irrigation frequency   of caisim hydroponic will given good yield and water productivity. Four level of irrigation frequency treatments were 1,3,5, and 7 times per day. The result of the research indicated that irrigation frequeny of 5 times per day of caisim hydroponic with carbonized rice hull media was obtained highest water productivity 7,45 kg m-3 compared to 1,3, and 7 times irrigation per day.  Irrigation frequency of 5 times per day was obtained good yield of caisim hydroponic is average 78,22 g/plant not significantly compared to yield of caisim non hydroponic with 1 times irrigation per day is average 80,78 g/plant.   Keywords: irrigation frequency, caisim, hydroponic, carbonized rice hull, production, and water productivity